1994
DOI: 10.1002/jsfa.2740650305
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the recovery of proteinaceous substances from chicken heads: II—Application of pepsin to the production of protein hydrolysate

Abstract: Minced heads of broiler chickens were hydrolysed under various conditions using porcine pepsin. It was found that hydrolysis goes at an optimum rate at 55°C and pH 1.5 following the addition of 750 g water and 3 g pepsin per kg raw material. After 5 h of proteolysis, 1 kg of the raw material yielded 144 g of dry unneutralised hydrolysate containing 15.7 g total nitrogen, equivalent to a 67.8% nitrogen recovery. Neutralisation prior to drying marginally decreased nitrogen recovery and reduced the nitrogen solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 10 publications
5
18
0
Order By: Relevance
“…2005). Similar observations have been reported for hydrolytic response of food proteins using animal or microbial proteases (Ferreira and Hultin 1994; Surowka and Fik 1994; Baek and Cadwallader 1995; Benjakul and Morrissey 1997).…”
Section: Resultssupporting
confidence: 87%
“…2005). Similar observations have been reported for hydrolytic response of food proteins using animal or microbial proteases (Ferreira and Hultin 1994; Surowka and Fik 1994; Baek and Cadwallader 1995; Benjakul and Morrissey 1997).…”
Section: Resultssupporting
confidence: 87%
“…[35] Foam stability for the different hydrolysates is shown in Table 3. The least foaming capacity and stability was shown by the Grass carp skin hydrolysate.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Benjakul & Morrissey (1997) revealed that an increase in fish waste: buffer ratio resulted in an increase in protein content and amino acid concentration of hydrolysate. Additionally, it may enhance endogenous enzyme homogeneity, reduce the localise concentration of hydrolysis product and promote tissue swelling (Surowka & Fik, 1994).…”
Section: Optimisation Condition For Hydrolysismentioning
confidence: 99%